Correction: miR-548as-5p promotes breast cancer cell apoptosis and improves tamoxifen resistance by downregulating NF-κB1 - Xu Chen; Meng Tao; Yu Zhuang; Junyi Zhao; Chang Yao; Dongchen Lu (Molecular Biology Reports, 2026)

miR-548as-5p promotes breast cancer cell apoptosis and improves tamoxifen resistance by downregulating NF-κB1 - Xu Chen; Meng Tao; Yu Zhuang; Junyi Zhao; Chang Yao; Dongchen Lu (Molecular Biology Reports, 2026)

​​Integrating machine learning and spatial transcriptomics uncovers shared immunomodulatory deubiquitinases in MAFLD and HCC - Yu-xi Han; Hongze Li; Wendi Xia; Junyi Ma; Jiaqi Zhang; Yiling Li (Human Genetics, 2026)

Selective recovery of palladium from actual acidic wastewater using a covalent triazine framework: The critical enabling role of chloride ions - Junyi Yu; Qingying Xiao; Ziwen Chang; Jianzhi Zhang; Hao Dong; Jiaochan Zhong; Lin Ding; Yidi Chen; Xubiao Luo; Penghui Shao (Water Research, 2026)

Aluminum mineral transformation drives reacidification and metal remobilization in a neutralized acidic pit lake - Junyi Gu; Lu Zhang; Ziyi Li; Rui Deng; Zijie Yu; Bo Wang; Zhengbo Yue; Jin Wang (Water Research, 2026)

Deciphering the potential molecular links between ochratoxin A and colorectal cancer: an integrated computational toxicological and single-cell transcriptomic study - Tianqi Qiu; Junyi Zhuo; Hua Wu; Min Lin; Kaisheng Zhang; Yu Tang (Toxicon, 2026)

ZIF-71-programmed hydrophobic capillary gating in polylactic acid (PLA) composite aerogels for recyclable oil-water separation - Junyi Shi; Hongjuan Wang; Peng Liu; Dehai Yu; Dandan Ji (Journal of Environmental Chemical Engineering, 2026)

Quantitative assessment of nanoplastic toxicity risks across aquatic trophic levels with data-driven models and exposure experiments - Zhenyu Wang; Zheng Tian; Yu Kong; Ning Liu; Zhenggao Xiao; Junyi Zhang; Xiaona Li; Baoshan Xing (Environmental Pollution, 2026)

Freeze-thaw propagation behavior of rock with cracks and a thermo-mechanical coupled phase-field fracture model - Zhitao Lv; Yu Chen; Jintao Liu; Shibing Huang; Junyi Duan; Yunlong Cai (Computers and Geotechnics, 2026)

Instability-driven flame propagation dynamics of premixed hydrogen-ammonia deflagration in a closed duct with obstacles - Rui Xie; Zhi Wang; Xianyu Yu; Liuqian Zhu; Yang Lin; Junyi Li; Bobo Shi (Fuel, 2026)

Ontogenetic shifts in salinity tolerance and metabolic strategies of Heliocidaris crassispina: implications for aquaculture management - Zirui Li; Qiyang Sun; Dejian Su; Yang Ming; Junyi Wen; Zonghe Yu (Aquaculture International, 2026)

Co-mitigating tire wear particles and their leachates across the life cycle: A critical review - Kejun Liao; Junyi Yu; Ruohan Huang; Wenjing Zhou; Yuwei Zhou; Junru Guo; Shengman Zhang; Chen Cai; Kaiming Peng; Xiangfeng Huang; Jia Liu (Water Research, 2026)

Multiscale molecular engineering of a thermogelling polymer integrating quantum mechanics, polymer chemistry and artificial intelligence - Tao Sun; Weihan Rao; Junyi Li; Lingxi Li; Yiman Wei; Shuquan Cui; Wenqian Li; Yanshuang Zhang; Yixuan Wang; Lin Yu; Jiandong Ding (Science Bulletin, 2026)

Cradle-to-gate life cycle assessment of cosmetic-grade hyaluronic acid in China via microbial fermentation: hotspots and mitigation levers - Junyi Shi; Chao Liu; Dehai Yu; Dandan Ji (The International Journal of Life Cycle Assessment, 2026)

Associations of serum per- and polyfluoroalkyl substances (PFAS) mixture with the risk of chronic diseases: evidence from single‑ , multi-pollutant, and machine learning models - Mei Li; Liting Sheng; Zige Ding; Guangsheng Yu; Yichu Chen; Qitian Chen; Wei Shao; Bingxin Liu; Mulong Du; Dongying Gu; Silu Chen; Junyi Xin; et al. (Archives of Toxicology, 2026)

Population responses to climate change in the marginal areas of the dryland in East Asia since the LGM - Yanyan Yu; Junyi Ge; Junyan Geng; Haibin Wu; Amber Johnson; Feng He; Zhengtang Guo (Quaternary Science Reviews, 2026)

Combined organic pollutants and heavy metals distinctly alter microbial assembly and metabolism of Cynodon dactylon (L.) Pers. within industrial green belts - Junyi Yu; Shuangqiang Li; Junru Guo; Ruohan Huang; Chen Cai; Kaiming Peng; Lijun Lu; Xiangfeng Huang; Jia Liu (Journal of Environmental Sciences, 2026)

Dual-anion synergy in solvation structure manipulation for high-voltage gel polymer electrolyte - Qiudian Liu; Wenxi Wu; Jiafan Guo; Xiaomin Su; Junyi Huang; Fengyun Nie; Hongfa Jiang; Feng Yu; Yong Chen (Chemical Engineering Journal, 2026)

Genome-characterized Lacticaseibacillus rhamnosus Hao9 alleviates DSS–induced chronic low-grade inflammation and modulates the gut microbiota - Minxin Yang; Jinyan Yu; Shengliang Wang; Xianyan Liao; Mei Han; Junyi Huang (Food Bioscience, 2026)

Ubiquitous intelligent optimization promotes sustainable food cold chain logistics: Research progress, challenges, and future trends - Qian Chen; Junyi Wang; Jiali Li; Zhouqiao Ren; Zihan Liu; Yan Wei; Wei Ma; Jiabin Yu; Jianping Qian (Trends in Food Science & Technology, 2026)

Hidden acidification beneath soil-covered mine waste dumps: links to oxygen-limited sulfur oxidation - Ziyi Li; Zhengbo Yue; Junyi Gu; Shu Wang; Lu Zhang; Zijie Yu; Rui Deng; Jin Wang (Journal of Environmental Management, 2026)

Insight into the mechanism of natural preservatives (rosmarinic acid and phytic acid) against quality deterioration of Pacific white shrimp through interactions with hemocyanin - Junpeng Zeng; Xiaowei Fan; Junyi Song; Yu Song; Peixu Cong; Yanjun Liu; Changhu Xue; Jie Xu (Food Chemistry, 2026)

Multi-indicator prediction of kiwifruit quality integrating hyperspectral analysis and WGAN-GP-MMoE framework - Zihan Liu; Qian Chen; Jiali Li; Haosong Liu; Boyu Shuai; Linghuan Ouyang; Zihan Bian; Junyi Wang; Jiabin Yu; Jianping Qian (Food Control, 2026)

Light-responsive brick-and-mortar nanofluidic membranes for high-power osmotic energy harvesting - Chao Liu; Junyi Shi; Zhaoqi Lin; Zhaoyun Lin; Linglong Shi; Weikun Jiang; Qiang Wang; Dandan Ji; Yu Liu; Dehai Yu (Chemical Engineering Journal, 2026)

Skin-triggered Janus physical cooling patches for prolonged evaporative cooling and superior comfort - Junyi Lu; Fuzhou Niu; Tonghuan Zhan; Heng Wang; Haojun Luo; Yichen Tang; He Wang; Xiaohua Yu; Weijie Zhang; Hao Chen; Bing Xu (Chemical Engineering Journal, 2026)

Ni/Biochar-catalyzed biomass gasification for process-compatible NOx reduction in cement pre-calciner: pathways and mechanisms - Hui Peng; Rongyu Wu; Junyi Zhou; Tongsheng Zhang; Jiawei Wang; Zhen Huang; Congxi Tao; Jiangxiong Wei; Qijun Yu (Journal of Cleaner Production, 2026)

Characteristics of gas emission and explosion risk for lithium iron phosphate batteries in a proof-confined chamber: Impact of methane concentration and state of charge - Zhi Wang; Xianyu Yu; Fei Ren; Jinxiong Chen; Junyi Li; Bo Yin; Bobo Shi (Fuel, 2026)

Genetic variants in VEGF gene family enhance colorectal cancer susceptibility via modulating metabolic pathways - Yutao Zhou; Zhutao Ding; Yichu Chen; Qian Gong; Bingxin Liu; Yu Shao; Silu Chen; Meilin Wang; Dongying Gu; Junyi Xin (Archives of Toxicology, 2026)

Deciphering the divergent roles of glycoside surfactants in alkali-activated persulfate remediation of phenanthrene: Mechanistic and practical implications - Wenjing Zhou; Shuangqiang Li; Junyi Yu; Liheng Yang; Hongxin Chen; Kaiming Peng; Chen Cai; Xiangfeng Huang; Jia Liu (Journal of Hazardous Materials, 2026)

Skarn-related sphalerite: Indium enrichment and key controlling factors - Junyi Wang; Guotao Sun; Jia-Xi Zhou; Hui Chen; Bing Yu; Kai Luo; Shiyu Liu; Ruiliang Wang (Journal of Asian Earth Sciences, 2026)

Study on the suppression and CO elimination effect of Co3O4 catalyst on coal dust-methane mixed explosion - Xiaoyu Chen; Yating Liu; Jiaxin Shi; Bingjie Wang; Shuo Gao; Junyi Li; Xuan Xu; Jian Li; Yu Zhang; Chuyuan Liu; Jiahao Li; Mingya Wen; et al. (Fuel, 2026)

Dipole-moment–guided ionic liquid passivation for efficient and stable CsSnI3 perovskite solar cells - Letian Dai; Zhiguo Zhang; Xiongjie Li; Haixuan Yu; Junyi Huang; Zhirong Liu; Yan Shen; Mingkui Wang (Chemical Engineering Journal, 2026)

Fine monitoring of winter wheat LAI through two-step fusion of UAV and Sentinel-2 images with interpretable machine learning methods - Yu Yao; Luyu Zhao; Xiang Gao; Hengbin Wang; Junyi Liu; Xiaodong Zhang; Yuanyuan Zhao; Shaoming Li; Zhe Liu (European Journal of Agronomy, 2026)

The impact of residential neighbor noise on cognitive health in Chinese cities - Yu Chen; Junyi Wang; Junpei Wu; Yatai Li; Jifu Lu; Lihong Zhang (Building and Environment, 2026)

Experimental study on splash erosion resistance of granite residual soil improved by microbially induced carbonate precipitation - Weiping Liu; Jiaxing Sun; Bin Gui; Yu Gan; Sihai Luo; Yu Su; Junyi Duan (Soil and Tillage Research, 2025)

Effects of apoptosis on quality changes of Larimichthys crocea postmortem storage with emphasis on cytochrome c-mediated lipid deterioration - Xiaowei Fan; Yu Song; Yanjun Liu; Junyi Song; Junpeng Zeng; Zhaojie Li; Jie Xu; Changhu Xue (Food Research International, 2025)

Kinetic simulation of NOx reduction in cement pre-calciner environment: Synergistic effect of multi-reductant, catalytic effect of raw meal, and their reaction mechanism - Hui Peng; Junyi Zhou; Rongyu Wu; Tongsheng Zhang; Danting Chen; Yue Tang; Congxi Tao; Jiangxiong Wei; Qijun Yu (Chemical Engineering Journal, 2025)

Integrative single-cell and bulk RNA-seq analysis identifies glycosyltransferases-related signature in triple negative breast cancer - Junyi Hu; Ningning Yuan; Zhenglan Huang; Yancheng Liu; Bohan Tu; Xinyue Yu; Tianli Hui; Guowei Zuo (Functional & Integrative Genomics, 2025)

Adaptive Feeding Strategies Facilitate Resilience of Deep‐Sea Cold Seep Molluscs Confronting Climate Change - Yu Chen; Yali Liu; Jie Li; Haiyan Yu; Junyi Yang; Qiqi Li; Lina Lyu; Si Zhang (Molecular Ecology, 2025)
Molluscs living in dynamic deep‐sea cold seep environments have evolved distinct feeding strategies for survival. Here, we present the chromosome‐level genomes of two sympatric mollusc species with distinct feeding strategies, a symbiosis‐dependent mussel Gigantidas haimaensis and a predatory snail Phymorhynchus buccinoides . Comparative genomic analysis revealed gene family expansions related to the bacterial component degradation (e.g., b4GalT s) in G. haimaensis , suggesting an adaptation to symbiotic life. Conversely, P. buccinoides exhibited gene family expansions associated with appetite regulation (e.g., ox2r ) and the digestive system (e.g., sult1 and chst ), indicating genetic modifications for deep‐sea predation. Furthermore, we conducted an in situ experiment mimicking a scenario in which ocean warming and sea‐level rise resulted in a mass methane leakage in deep‐sea cold seeps. Interestingly, G. haimaensis increased its metabolic rate and exhibited transcriptional responses. However, P. buccinoides suppressed energy production and responses at translational and posttranslational levels, which is compatible with their distinct feeding strategies. Collectively, our results provide insights on the evolutionary basis and resilience mechanisms related to energy management, which may facilitate methane tolerance of molluscs in the deep‐sea cold seeps threatened by climate change.

A novel Toll-like receptor in Hyriopsis cumingii responds to Aeromonas veronii GL1 infection by the MyD88 signaling pathway - Junyi Lu; Qinglin Yang; Tao Wang; Guihong He; Xiaobo Yu; Zhengli Wu; Yanhong Li (Fish & Shellfish Immunology, 2025)

Prediction on the seismic behaviour of a multi-stage anchored slope by a time-dependent displacement analysis - Yu-Liang Lin; Li Lu; Dan He; Xiaobin Chen; JunYi Duan (European Journal of Environmental and Civil Engineering, 2025)

Waste heat-driven persulfate activation for actual landfill leachate concentrates: performance and mechanisms - Zhenyu Luo; Xinkai Yuan; Junyi Yu; Minkang Hu; Yingying Zhou; Yi Gong; Jintao Wang; Xiaoxuan Ye; Guanyuan Gao; Penghui Shao; Xubiao Luo (Chemical Engineering Journal, 2025)

Exploring the biocontrol performance of Bacillus velezensis against postharvest diseases of eggplants and the underlying action mechanisms in soft rot management - Xiaoyun Zhang; Junyi Wang; Yu Xin; Esa Abiso Godana; Solairaj Dhanasekaran; Ruijie Luo; Jun Li; Lina Zhao; Hongyin Zhang (Postharvest Biology and Technology, 2025)

Numerical study of a cold start at the ambient temperature of 243 K on methanol engine with coolant heating - Junyi Liu; Qinglong Yu; Junjie Cheng; Abubakar Unguwanrimi Yakubu; Xuanhong Ye; Shusheng Xiong (Fuel, 2025)

Simultaneous solar-driven steam and electricity generation by CNT/Zn2+-intercalated graphene oxide membranes - Yanmei Zhu; Jiali Lan; Yuping Du; Tao Yang; Hairong Yu; Ting Liang; Xingbin Lv; Changjing Cheng; Junyi Ji (Chemical Engineering Journal, 2025)

Future Climate Change Impacts on Extreme Precipitation: Exposure Risks for Urban Populations and Cropland in North China - Changwen Yu; Wenqian Zhang; Nan Song; Guwei Zhang; Jiajun Yao; Zhiqi Xu; Junyi Xiu (International Journal of Climatology, 2025)
North China faces increasing risks from extreme precipitation under climate change, yet projections integrating socio‐economic dynamics with high‐resolution climate models remain limited. Leveraging the latest version of the NEX‐GDDP‐CMIP6 (NASA Earth Exchange Global Daily Downscaled Projections) from NASA (National Aeronautics and Space Administration) and CMIP6 (Coupled Model Intercomparison Project Phase 6) datasets across SSP1‐2.6, SSP2‐4.5 and SSP5‐8.5 scenarios, this study quantifies future extreme precipitation impacts on urban populations and cropland in two critical periods: 2031–2050 (mid‐century) and 2081–2100 (end‐century). Through the Multivariable Integrated Evaluation Tool (MVIETool), we demonstrate that NEX‐GDDP‐CMIP6 reduces regional precipitation biases by 79% compared to CMIP6 (from +133.16 mm/day to −27.00 mm/day), despite persistent uncertainties in extreme intensity indices. Projections reveal a pronounced intensification of extreme precipitation, with R99p (extremely wet day precipitation) increasing by 127%–131% and CDD (consecutive dry days) decreasing by 12%–17% in 2081–2100 under SSP5‐8.5, signalling a transition toward wetter conditions. Exposure analyses indicate that 38.24 million citizens (26.32% of the urban population) and 49,900 km 2 cropland (5.87% of the area) in North China may face record‐breaking precipitation events by the end of the century under SSP5‐8.5, primarily concentrated in coastal megacities and the North China Plain. These findings underscore the urgency of scenario‐specific adaptation strategies, including ‘sponge city’ retrofitting in high‐exposure zones and precision agriculture tailored to precipitation regime shifts. Our integrated framework advances regional climate risk assessments by reconciling dynamical downscaling limitations with SSP‐driven socio‐economic uncertainties.

Highly stretchable, self-adhesive, conductive, and tough hydrogel reinforced with cellulose nanofibers for wearable biosensor and ultrasonic nanogenerator - Yijun Fu; Junyi Zou; Yijie Wang; Zhengyu Yao; Pengfei Lv; Dingsheng Wu; Qufu Wei; Wei Zhang; Yu Jiang; Dawei Li (Chemical Engineering Journal, 2025)

The new insight into the impact of hemocyanin on quality deterioration of Pacific white shrimp during refrigerated storage - Xiaowei Fan; Junyi Song; Yu Song; Yanjun Liu; Junpeng Zeng; Jie Xu; Changhu Xue (Food Chemistry, 2025)

Effects of low light, interspecific competition, and their combination on flavonoid exudation patterns and rhizosphere fungal community in Juglans mandshurica and Fraxinus mandshurica roots - Liqing Xu; Yong Zhang; Nowsherwan Zarif; Hongli Li; Donghai Cui; Junyi Yu; Jiajin Duan; Changzhun Li; Qingcheng Wang (Plant and Soil, 2025)

Experimental investigation of the heave behaviors of ballastless railways on expansive soil foundations - Junyi Duan; Shengji Liang; Yu Su; Yuliang Lin; Weiping Liu; Gang Wang; Li Lu (Transportation Geotechnics, 2025)

Molecular size matching of dopant in polypyrrole and anion in dual-ion battery enhancing the energy storage ability and dynamics of polypyrrole cathode - Feng Yu; Xuezheng Chen; Junyi Huang; Hongfa Jiang; Wen Chen; Yong Chen (Chemical Engineering Journal, 2025)

Effects of mitochondrial lipidome alterations on quality deterioration of Larimichthys crocea postmortem storage: New insight from the perspective of mediating mitochondria-dependent apoptosis - Xiaowei Fan; Yu Song; Yanjun Liu; Junyi Song; Junpeng Zeng; Zhaojie Li; Jie Xu; Changhu Xue (Food Chemistry, 2025)

Applicability of various organic and mineral materials for sustainable remediation of degraded coal mining soil - Junyi Feng; Tian Yu; Jing Tan; Mengmeng Zhao; Zhanbin Huang (Journal of Soils and Sediments, 2025)

The path of corporate low-carbon behavioral change: The impact of digital transformation on corporate green sports brand loyalty - Junyi Li; Zhengfan Xie; Yu Fu (Journal of Environmental Management, 2025)

The combined effects of microplastics and their additives on mangrove system: From the sinks to the sources of carbon - Junru Guo; Mingqing Yang; Ruohan Huang; Junyi Yu; Kaiming Peng; Chen Cai; Xiangfeng Huang; Qiaofeng Wu; Jia Liu (Science of The Total Environment, 2025)

Classifying zircon: A machine-learning approach using zircon geochemistry - Jintao Kong; Hongru Yu; Junyi Sun; Huan Zhang; Miaomiao Zhang; Zhi Xia (Gondwana Research, 2025)

MsDUF3700 overexpression enhances aluminum tolerance in alfalfa shoots - Jiamin Cao; Tingting Wang; Dian Yu; Junyi He; Wenwu Qian; Bingxia Tang; Xiaojing Bi; Hui Wang; Yunwei Zhang (Plant Cell Reports, 2024)

Ferroptosis and its emerging role in kidney stone formation - Junyi Yang; Weisong Wu; Yirixiatijiang Amier; Xianmiao Li; Wenlong Wan; Yang Xun; Xiao Yu (Molecular Biology Reports, 2024)
Kidney stone is a common and highly recurrent disease in urology, and its pathogenesis is associated with various factors. However, its precise pathogenesis is still unknown. Ferroptosis describes a form of regulated cell death that is driven by unrestricted lipid peroxidation, which does not require the activation of caspase and can be suppressed by iron chelators, lipophilic antioxidants, inhibitors of lipid peroxidation, and depletion of polyunsaturated fatty acids. Recent studies have shown that ferroptosis plays a crucial role in kidney stone formation. An increasing number of studies have shown that calcium oxalate, urate, phosphate, and selenium deficiency induce ferroptosis and promote kidney stone formation through mechanisms such as oxidative stress, endoplasmic reticulum stress, and autophagy. We also offered a new direction for the downstream mechanism of ferroptosis in kidney stone formation based on the “death wave” phenomenon. We reviewed the emerging role of ferroptosis in kidney stone formation and provided new ideas for the future treatment and prevention of kidney stones.

Effect of lipid oxidation on quality attributes and control technologies in dried aquatic animal products: a critical review - Junpeng Zeng; Yu Song; Xiaowei Fan; Jingyi Luo; Junyi Song; Jie Xu; Changhu Xue (Critical Reviews in Food Science and Nutrition, 2024)

Effect of cytochrome c release on the mitochondrial-dependent apoptosis and quality deterioration of black rockfish (Sebastes schlegelii) postmortem storage - Xiaowei Fan; Yu Song; Yanjun Liu; Junyi Song; Junpeng Zeng; Zhaojie Li; Jie Xu; Changhu Xue (Food Chemistry, 2024)

Toward high-purity vanadium-based materials: Fundamentals, purifications, and perspectives - Jin Wang; Wenhao Yu; Junyi Xiang; Weizao Liu; Dapeng Zhong; Shengming Xu; Xuewei Lv (Journal of Cleaner Production, 2024)

Shear behaviors of expansive soils over a wide confining pressures range and their impacts on strength parameters - Junyi Duan; Junjiang Wu; Yu Su; Yuliang Lin; Yafeng Li; Li Lu (Transportation Geotechnics, 2024)

Visual analysis of sea buckthorn fruit moisture content based on deep image processing technology - Yu Xu; Xuhai Yang; Junyi Zhang; Xiang Zhou; Liwei Luo; Qian Zhang (Food Chemistry, 2024)

Thin film AgBiS2 solar cells with over 10 % power conversion efficiency enabled by vapor-assisted solution process treatment - Xiongjie Li; Haixuan Yu; Xiaoting Ma; Zhirong Liu; Junyi Huang; Yan Shen; Mingkui Wang (Chemical Engineering Journal, 2024)

Stabilization/solidification of radioactive borate waste via low-carbon limestone calcined clay cement (LC3) - Jian Wang; Daquan Shi; Yan Xia; Minghao Liu; Xiaobing Ma; Kunyang Yu; Yading Zhao; Junyi Zhang (Journal of Environmental Chemical Engineering, 2024)

Humidity-resistant, breathable, waterproof, and bionic triboelectric electronic skins for self-powered haptic sensing and human motion recognition - Xia Liu; Yulong Wang; Wei Wang; Meifei Cheng; Aifang Yu; Lingyu Wan; Junyi Zhai (Chemical Engineering Journal, 2024)

Over 12% efficient CsSnI3 perovskite solar cells enabled by surface post-treatment with bi-functional polar molecules - Zhiguo Zhang; Haixuan Yu; Junyi Huang; Zhirong Liu; Qiang Sun; Xiongjie Li; Letian Dai; Yan Shen; Mingkui Wang (Chemical Engineering Journal, 2024)

The auxin response factor (ARF) gene family in Cyclocarya paliurus: genome-wide identification and their expression profiling under heat and drought stresses - Ziyong Gao; Yazhu Wu; Muzi Li; Lan Ding; Junyi Li; Ying Liu; Yu Cao; Yangguang Hua; Qiaojun Jia; Dekai Wang (Physiology and Molecular Biology of Plants, 2024)

Transcription and splicing variations of SR genes accompany with genome-wide accumulation of long-introns in pine - Shanlan Chen; Yingjie Zhang; Li Liu; Yujian Mo; Junyi Li; Beibei Chen; Yi Zhou; Jinxing Lin; Xingyu Jiang; Long Wei; Yu Ling (Plant Science, 2024)

Determinants of Aggregated Embodied Carbon Intensity in Global Bilateral Exports by Firm Heterogeneity - Ya-Fang Sun; Bin Su; Sheng Zhong; Junyi He; Shiwei Yu (Ecological Economics, 2024)

Intramolecular generation of endogenous Cu(III) for selectively self-catalytic degradation of Cu(II)-EDTA from wastewater by UV/peroxymonosulfate - Junyi Yu; Wei Deng; Xianfeng Huang; Min Zhao; Xuchun Li; Tao Zhang; Bingcai Pan (Journal of Hazardous Materials, 2024)

Metallic nanoparticles synthesized by algae: Synthetic route, action mechanism, and the environmental catalytic applications - Jiajun Wen; Fengyu Gao; Hengheng Liu; Junyi Wang; Tingkai Xiong; Honghong Yi; Yuansong Zhou; Qingjun Yu; Shunzheng Zhao; Xiaolong Tang (Journal of Environmental Chemical Engineering, 2024)

Ultra-high output triboelectric nanogenerator based on synergies of material modification and charge pumping - Zekun Li; Jitao Liu; Mengshuang Chi; Xue Miao; Hanxiao Yang; Weiqi Cui; Aifang Yu; Junyi Zhai (Chemical Engineering Journal, 2024)

Comprehensive Evaluation of In Situ Stress in the Daning–Jixian Area and Its Control on the Distribution of Coal-Measure Gas - Zheng Zhao; Dameng Liu; Bo Wang; Ming Chen; Junyi Sun; Lizhu Yu; Yidong Cai; Xiaozhou Zhang; Xiaolei Wu; Fengrui Sun (Natural Resources Research, 2024)

Application of skeleton builders to sludge dewatering and disposal: A critical review - Purui Bao; Chunyan Du; Yifu Li; Heng Jiang; Lu Zhou; Guanlong Yu; Shiquan Sun; Lean Zhou; Xue Li; Junyi Teng; Xiaowen Wang; Junchao Wang (Science of The Total Environment, 2024)

Characterization of a Bacillus velezensis strain as a potential biocontrol agent against soft rot of eggplant fruits - Xiaoyun Zhang; Yu Xin; Junyi Wang; Solairaj Dhanasekaran; Qingrong Yue; Faping Feng; Xiangyu Gu; Bo Li; Lina Zhao; Hongyin Zhang (International Journal of Food Microbiology, 2024)

Characteristic aroma-active components of fried green onion (Allium fistulosum L.) through flavoromics analysis - Jing Wang; Lina Qiao; Bing Liu; Junyi Wang; Ruifang Wang; Ning Zhang; Baoguo Sun; Haitao Chen; Yang Yu (Food Chemistry, 2023)

Extraction of triterpene acids from loquat leaves via a novel hydrophobic deep eutectic solvent screened by COSMO-SAC model - Lu Huang; Yingjie Guo; Tianqi Jin; Ke Yan; Xianglin Liu; Shuyang He; Lin Li; Ye Gong; Junyi Ma; Hang Yu; Zhoumin Lu; Yupeng Liu; et al. (Journal of Cleaner Production, 2023)

Application of spectrochemical analysis with chemometrics to profile biochemical alterations in nanoplastic-exposed HepG2 cells - Yu Xing; Jing Li; Jingjing Yang; Junyi Li; Weiyi Pang; Francis L. Martin; Li Xu (Environmental Pollution, 2023)

Evolution stage identification of haze pollution episodes in beijing using constrained dynamic time warping and multiway principal component analysis - Hao Zhang; Yilun Lin; Jinye Ran; Junyi Yu; Morui Zhu; Hengqi Li; Yongli Jiao (Environmental Modelling & Software, 2023)

Spatial pattern assessment of dengue fever risk in subtropical urban environments: The case of Hong Kong - Shi Yin; Junyi Hua; Chao Ren; Runxi Wang; André Ibáñez Weemaels; Benoit Guénard; Yuan Shi; Tsz-Cheung Lee; Hsiang-Yu Yuan; Ka Chun Chong; Linwei Tian (Landscape and Urban Planning, 2023)

Integrated transcriptome and proteome analysis the molecular mechanisms of nutritional quality in ‘Chenggu-32’ and ‘Koroneiki’ olives fruits (Olea europaea L.) - Xin Miao; Junyi Ma; Xin Miu; Hongjie Zhang; Yinxin Geng; Wei Hu; Yu Deng; Na Li (Journal of Plant Physiology, 2023)

Phytochemical profiling and antioxidant, enzyme-inhibitory, and toxic activities of extracts from Adonis ramosa Franch - Xin Guo; Meihua Chen; Xu He; Yiman Zhao; Jianhua Yu; Junyi Zhu; Li Li; Guangqing Xia; Hao Zang (Natural Product Research, 2023)

Multiple textile triboelectric nanogenerators based on UV-protective, radiative cooling, and antibacterial composite yarns - Meifei Cheng; Xia Liu; Zekun Li; YiLin Zhao; Xue Miao; Hanxiao Yang; Tao Jiang; Aifang Yu; Junyi Zhai (Chemical Engineering Journal, 2023)

Metabolomics analysis reveals cytotoxic effects of ouabain towards psoriatic keratinocytes via impairment of glutathione metabolism - Xuan Zhou; Fei Fei; Wei Song; Hehua Ma; Zhenzhen Xu; Jing Yue; Bei Cao; Runbin Sun; Yu Zhao; Yuanxun Yang; Junyi Jiang; Yan Geng; et al. (Molecular Genetics and Genomics, 2023)
Ouabain is a cardiac glycoside long studied for treating heart diseases, but the attempts to evaluate its anti-psoriatic activity have not been reported. We aimed to explore the effects of ouabain on proliferation and metabolism towards psoriatic keratinocytes. In human HaCaT keratinocytes, ouabain potently decreased viability, promoted apoptosis and caused G2/M cycle arrest. Metabolomics analysis indicated that ouabain markedly impaired glutathione metabolism. The solute carrier family 7 member 11 (SLC7A11) is an amino acid transporter highly specific to cysteine, which is critical for glutathione synthesis. Ouabain downregulated SLC7A11, reduced cysteine uptake and subsequently inhibited glutathione synthesis, probably through inhibiting Akt/mTOR/beclin axis that regulate protein activity of SLC7A11. The impaired glutathione synthesis and oxidative stress caused by ouabain may contribute to its cytotoxicity towards psoriatic keratinocytes. Our results provide experimental evidence supporting further study of ouabain as a potential anti-psoriatic agent.

Mechanism and security of UV driven sodium percarbonate for sulfamethoxazole degradation using DFT and metabolomic analysis - Xiaolong Yu; Xu Jin; Meng Li; Yuanyuan Yu; Hang Liu; Rujin Zhou; Aiguo Yin; Junyi Shi; Jianteng Sun; Lizhong Zhu (Environmental Pollution, 2023)

Improved utilization of Cu0 for efficient adsorption of iodine in gas and solution by mesoporous Cu0-SBA-15 via solvothermal reduction method - Xinmiao He; Li Chen; Xin Xiao; Yi Gan; Jiaping Yu; Junyi Luo; Hui Dan; Yujie Wang; Yi Ding; Tao Duan (Chemical Engineering Journal, 2023)

Accurate and rapid quantification of PD-L1 positive exosomes by a triple-helix molecular probe - Zhichao Fan; Qin Weng; Yingxue Li; Tian Zeng; Junyi Wang; Honglan Zhang; Hua Yu; Yan Dong; Xiang Zhao; Jianjun Li (Analytica Chimica Acta, 2023)

Soil Aggregate Size Distribution Alters CO2 but not N2O Emission Rates in Chinese Fir (Cunninghamia lanceolata) Plantations with N and P Additions - Junyi Xie; Mengyun Chen; Ling Zhang; Yun Niu; Xiaojun Liu; Laicong Luo; Yu Zou; Xiaofei Hu; Xiaomin Guo; Evan Siemann (Journal of Soil Science and Plant Nutrition, 2023)

Ship-to-ship maritime wireless channel modeling under various sea state conditions based on REL model - Fang Li; Yishui Shui; Jiayao Liang; Kun Yang; Junyi Yu (Frontiers in Marine Science, 2023)
The propagation of electromagnetic waves on land and sea is significantly different. Although the Los scenario is significant in marine wireless communication, the marine wireless channel exists an obvious two-ray phenomenon due to the strong reflection path reflected through the sea surface. By modeling the measured data of marine wireless channels, this paper calculates the radio propagation characteristics of the Pearl River estuary. In addition, the wave fluctuations and high humidity environment will also impact the properties of the marine wireless channel. Therefore, sea surface morphology models under multiple wind speeds are built. To estimate the path loss in the same area under different conditions, the Monte Carlo method is employed to quantify the results. The simulation results show that the electric wave propagation gradually degenerated from the round earth loss (REL) model to the free space model with increasing wind speed. Moreover, the distribution of the shadow fading varies with distance. The findings provide references for the network planning of marine communication.

Climatic factors and human population changes in Eurasia between the Last Glacial Maximum and the early Holocene - Yanyan Yu; Feng He; Stephen J. Vavrus; Amber Johnson; Haibin Wu; Wenchao Zhang; Qiuzhen Yin; Junyi Ge; Chenglong Deng; Michael D. Petraglia; Zhengtang Guo (Global and Planetary Change, 2023)

Effects of different particle-sized insoluble dietary fibre from citrus peel on adsorption and activity inhibition of pancreatic lipase - Ben Yu; Qingmiao Tang; Caixia Fu; Joe Regenstein; Junyi Huang; Lufeng Wang (Food Chemistry, 2023)

Enhanced breakdown strength and electrostatic energy density of polymer nanocomposite films realized by heterostructure ZnO-ZnS nanoparticles - Jie Liu; Linye Ji; Junyi Yu; Shanjun Ding; Suibin Luo; Baojin Chu; Jianbin Xu; Rong Sun; Shuhui Yu (Chemical Engineering Journal, 2023)

Slaking and disintegration behavior of mudstone: insights from laboratory experiment and orthogonal images - Junyi He; Yangyang Leng; Yong Wu; Wenbin Chang; Yu Zhuang; Fengchai Zou (Bulletin of Engineering Geology and the Environment, 2022)

Rocky desertification poverty in Southwest China: Progress, challenges and enlightenment to rural revitalization - Taian Zuo; Fengtai Zhang; Junyi Zhang; Lei Gao; Shijie Yu (Journal of Geographical Sciences, 2022)

Evaluation of total phenolic, flavonoid, carbohydrate contents and antioxidant activities of various solvent extracts from Angelica amurensis root - Luyun Zhang; Junlin Yu; Qian Xu; Junyi Zhu; Hui Zhang; Guangqing Xia; Hao Zang (Natural Product Research, 2021)

Analysis of Dangchuan 5# landslide on January 27, 2021, in Yongjing County, Gansu Province, China - Wenbin Chang; Aiguo Xing; Ping Wang; Yu Zhuang; Kaiping Jin; Junyi He; Shaofeng Chai (Landslides, 2021)

Investigation of Characteristics of Long Runout Landslides Based on the Multi-source Data Collaboration: A Case Study of the Shuicheng Basalt Landslide in Guizhou, China - Yu Zhuang; Aiguo Xing; Yangyang Leng; Muhammad Bilal; Yanbo Zhang; Kaiping Jin; Junyi He (Rock Mechanics and Rock Engineering, 2021)

Maritime Broadband Communication: Wireless Channel Measurement and Characteristic Analysis for Offshore Waters - Changzhen Li; Junyi Yu; Jie Xue; Wei Chen; Shoufeng Wang; Kun Yang (Journal of Marine Science and Engineering, 2021)
For a long time, the development of maritime communication has been restricted by the low data rate, high-latency and high cost of the current communication systems. The upgrade of new generation mobile communication technologies is attracting more and more attention to conduct a shore-based broadband mobile communication network with high-latency and high reliability to serve the maritime industries. This paper presents a solution by means of building a ship-to-infrastructure (S2I) and a ship-to-ship (S2S) wireless communication networks for an offshore region. We characterize the S2I and S2S channels at 5.9 GHz band based on the channel measurements in realistic environments. The channel characteristics, including power delay profile, delay spread, propagation path loss, are extracted and analyzed. In view of the difference between marine and terrestrial communications, we analyze the influencing factors of the offshore water, including effective reflection, divergence and shadowing from the water surface, and diffraction loss caused by the earth curvature. We also predict the power coverage range and the channel capacity for S2I and S2S wireless communications. Finally, the communication performance is evaluated according to the channel measurement and characterization analysis. The research results can be a reference for the construction of maritime communication networks.

Chemical composition and biological activities of an essential oil from the aerial parts of Artemisia Gmelinii weber ex Stechm - Qian Xu; Luyun Zhang; Shuai Yu; Guangqing Xia; Junyi Zhu; Hao Zang (Natural Product Research, 2021)

miR156b from Soybean CMS Line Modulates Floral Organ Development - Xianlong Ding; Hui Ruan; Lifeng Yu; Qiang Li; Qijian Song; Shouping Yang; Junyi Gai (Journal of Plant Biology, 2020)

Frequency Characteristics and Numerical Computation of Seismic Records Generated by a Giant Debris Flow in Zhouqu, Western China - Xinghui Huang; Zhengyuan Li; Junyi Fan; Dan Yu; Qiang Xu (Pure and Applied Geophysics, 2020)

Efficient QTL detection of flowering date in a soybean RIL population using the novel restricted two-stage multi-locus GWAS procedure - Liyuan Pan; Jianbo He; Tuanjie Zhao; Guangnan Xing; Yufeng Wang; Deyue Yu; Shouyi Chen; Junyi Gai (Theoretical and Applied Genetics, 2018)

Comparative Flower and Inflorescence Organogenesis among Genera of Betulaceae: Implications for Phylogenetic Relationships - Junyi Zhu; Lifan Zhang; Baoqing Ren; Min Chen; Ruiqi Li; You Zhou; Yu Liang; Jianhua Li; Zhiduan Chen (The Botanical Review, 2018)

Dynamic monitoring and prediction of Dianchi Lake cyanobacteria outbreaks in the context of rapid urbanization - Yi Luo; Kun Yang; Zhenyu Yu; Junyi Chen; Yufei Xu; Xiaolu Zhou; Yang Yang (Environmental Science and Pollution Research, 2017)

Cloning and functional analysis of two GmDeg genes in soybean [Glycine max (L.) Merr.] - Xing Kong; Jingyao Zhang; Deyue Yu; Junyi Gai; Shouping Yang (Journal of Plant Biology, 2017)

Structural Asymmetry of Dorsolateral Prefrontal Cortex Correlates with Depressive Symptoms: Evidence from Healthy Individuals and Patients with Major Depressive Disorder - Wei Liu; Yu Mao; Dongtao Wei; Junyi Yang; Xue Du; Peng Xie; Jiang Qiu (Neuroscience Bulletin, 2016)

Elevation‐induced climate change as a dominant factor causing the late Miocene C 4 plant expansion in the Himalayan foreland - Haibin Wu; Zhengtang Guo; Joël Guiot; Christine Hatté; Changhui Peng; Yanyan Yu; Junyi Ge; Qin Li; Aizhi Sun; Deai Zhao (Global Change Biology, 2014)
During the late Miocene, a dramatic global expansion of C 4 plant distribution occurred with broad spatial and temporal variations. Although the event is well documented, whether subsequent expansions were caused by a decreased atmospheric CO 2 concentration or climate change is a contentious issue. In this study, we used an improved inverse vegetation modeling approach that accounts for the physiological responses of C 3 and C 4 plants to quantitatively reconstruct the paleoclimate in the Siwalik of Nepal based on pollen and carbon isotope data. We also studied the sensitivity of the C 3 and C 4 plants to changes in the climate and the atmospheric CO 2 concentration. We suggest that the expansion of the C 4 plant distribution during the late Miocene may have been primarily triggered by regional aridification and temperature increases. The expansion was unlikely caused by reduced CO 2 levels alone. Our findings suggest that this abrupt ecological shift mainly resulted from climate changes related to the decreased elevation of the Himalayan foreland.

Constitution of resistance to common cutworm in terms of antibiosis and antixenosis in soybean RIL populations - Hyunjee Kim; Guangnan Xing; Yufeng Wang; Tuanjie Zhao; Deyue Yu; Shouping Yang; Yan Li; Shouyi Chen; Reid G. Palmer; Junyi Gai (Euphytica, 2014)

Genetic components and major QTL confer resistance to bean pyralid (Lamprosema indicata Fabricius) under multiple environments in four RIL populations of soybean - Guangnan Xing; Bin Zhou; Yufeng Wang; Tuanjie Zhao; Deyue Yu; Shouyi Chen; Junyi Gai (Theoretical and Applied Genetics, 2012)

Reconstructions of annual summer precipitation and temperature in north-central China since 1470 AD based on drought/flood index and tree-ring records - Liang Yi; Hongjun Yu; Junyi Ge; Zhongping Lai; Xingyong Xu; Li Qin; Shuzhen Peng (Climatic Change, 2012)

Genetic structure composed of additive QTL, epistatic QTL pairs and collective unmapped minor QTL conferring oil content and fatty acid components of soybeans - Haiwang Li; Tuanjie Zhao; Yufeng Wang; Deyue Yu; Shouyi Chen; Ruibao Zhou; Junyi Gai (Euphytica, 2011)

Isolation and Functional Characterization of a SERK Gene from Soybean (Glycine max (L.) Merr.) - Chao Yang; Tuanjie Zhao; Deyue Yu; Junyi Gai (Plant Molecular Biology Reporter, 2011)

Detection of quantitative trait loci for phosphorus deficiency tolerance at soybean seedling stage - Dan Zhang; Hao Cheng; Leiyue Geng; Guizhen Kan; Shiyou Cui; Qingchang Meng; Junyi Gai; Deyue Yu (Euphytica, 2009)

Identification and characterization of class 1 DXS gene encoding 1-deoxy-d-xylulose-5-phosphate synthase, the first committed enzyme of the MEP pathway from soybean - Man Zhang; Kai Li; Chunhong Zhang; Junyi Gai; Deyue Yu (Molecular Biology Reports, 2009)

Somatic embryogenesis and plant regeneration in Chinese soybean (Glycine max (L.) Merr.)—impacts of mannitol, abscisic acid, and explant age - Chao Yang; Tuanjie Zhao; Deyue Yu; Junyi Gai (In Vitro Cellular & Developmental Biology - Plant, 2009)

Characterization of O-Acetylserine(Thiol)Lyase-Encoding Genes Reveals Their Distinct but Cooperative Expression in Cysteine Synthesis of Soybean [Glycine max (L.) Merr.] - Chunhong Zhang; Qingchang Meng; Man Zhang; Fang Huang; Junyi Gai; Deyue Yu (Plant Molecular Biology Reporter, 2008)

Cloning and functional characterization of an O-acetylserine(thiol)lyase-encoding gene in wild soybean (Glycine soja) - Chunhong Zhang; Qingchang Meng; Junyi Gai; Deyue Yu (Molecular Biology Reports, 2008)

Constitutive overexpression of AOS-like gene from soybean enhanced tolerance to insect attack in transgenic tobacco - Juanjuan Wu; Qian Wu; Qiaojuan Wu; Junyi Gai; Deyue Yu (Biotechnology Letters, 2008)

Genome-wide identification and characterization of putative cytochrome P450 genes in the model legume Medicago truncatula - Lingyong Li; Hao Cheng; Junyi Gai; Deyue Yu (Planta, 2007)

GmZFP1 encoding a single zinc finger protein is expressed with enhancement in reproductive organs and late seed development in soybean (Glycine max) - Fang Huang; Yingjun Chi; Qingchang Meng; Junyi Gai; Deyue Yu (Molecular Biology Reports, 2006)

Mapping of SMV resistance gene Rsc-7 by SSR markers in soybean - Sanxiong Fu; Yong Zhan; Haijian Zhi; Junyi Gai; Deyue Yu (Genetica, 2006)